Korelasi Kebijakan Pemerintah, Kesadaran Halal dan Kompensasi Terhadap Kompetensi Pendamping Produk Halal : Pengembangan Sumber Daya Manusia Sebagai Variabel Intervening - Hidayati, Ulfa; Muthiadin, Cut; Thaha, Aminah Hajah; Fachrurrazy, Muhammad (Jurnal Ilmiah Ekonomi Islam, 2025)
Indonesia is intensifying the acceleration of halal certification in Indonesia to realize Indonesia as the Number 1 Halal Food and Beverage Producer in the world, and this hope is targeted to be carried out in 2024. Through this acceleration program, it directly has a positive implication in accelerating the inclusion of strengthening halal literacy in society. This study examines the Correlation of Government Policy, Halal Awareness and Compensation on Halal Product Companion Competence: Human Resource Development as an Intervening Variable. The research method uses Quantitative Descriptive, with 50 respondents. The results of the study indicate that Government Policy has a negative and insignificant effect on P3H Competence, Halal Awareness has a negative or indirect and insignificant effect on P3H Competence. Compensation has a positive or indirect but insignificant effect on P3H Competence. Government Policy has a positive or indirect but insignificant effect on P3H Human Resource Development. Halal Awareness has a positive or indirect and significant effect on P3H Human Resource Development. Compensation has a positive or indirect and significant effect on P3H Human Resource Development. Human resource development has a positive or unidirectional and significant effect on P3H Competence. The indirect effect of Government Policy through Human Resource Development on P3H Competence is positive but not significant. The indirect effect of Halal Awareness through Human Resource Development on P3H Competence is positive but not significant. The indirect effect of Compensation through Human Resource Development on P3H Competence is positive but not significant.